Online learning during the covid-19 pandemic: a survey study on student perceptions - Nurrahmawati Nurrahmawati; Ria Karno; Arcat Arcat; Lusi Eka Afri (Jurnal Konseling dan Pendidikan, 2025)
The COVID-19 pandemic has changed the higher education system. Initially, the learning process was conducted offline, where students engaged in face-to-face interaction. However, due to the pandemic, the learning system shifted to an online format. This study aims to determine student perceptions of online learning during the COVID-19 pandemic, assessed in terms of the following aspects: preferred learning media in online learning, knowledge or understanding, social competence, media usage skills, and obstacles encountered in online learning. This research employed a descriptive quantitative research. This study invited 187 students of the Faculty of Teacher Training and Education to fill an online survey administered through Google Forms. The online survey method was used for data collection purpose. Data analysis revealed that the online learning platform students preferred most was WhatsApp, as it allowed them to  save internet quota. Students' understanding of lecture materials during online learning was still lacking, their social competence did not increase, but their ability to use technology during online learning increased. The most dominant obstacles were technical problems, particularly network problems and limited internet quota. However, students still preferred offline learning to online learning. Therefore, in learning, lecturers should be able to combine both modes of learning, and provide online learning that can minimize internet data usage.